Pengaruh Ekonomi Orangtua Terhadap Motivasi Belajar Matematika Siswa Kelas VIII SMP Negeri 9 Padangsidimpuan - Nirma Wahyuni; Suparni Suparni (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2017)
Many of the effects of the economy are family resilience, family resilience is realized because the functioning of the family in meeting all physical and psychological needs, namely economic needs, education, hereditary instincts, instincts of compassion, protection and social affection. If the family's resilience has begun to be fragile it will have a bad influence on students' learning motivation if the child's learning motivation is no longer there and how to carry out education well. Therefore, as a component of education for both parents, the teacher must know the mentality of the child in order to be able to carry out education as well as possible.This study aims to determine the economics of parents in Padangsidimpuan 9th Middle School. To find out the motivation to learn Grade VIII Mathematics of SMP Negeri 9 Padangsidimpuan.This study uses a correlational method with a quantitative type, which provides an overview and simultaneously sees the influence of the two variables by calculating the mean, median, mode, variance and standard deviation. To provide an interpretation of the distribution of data obtained from the population are all class VIII SMP N 9 Padangsidimpuan about 227 students. The sampling technique carried out by researchers with cluster random sampling samples consisted of 45 VIII1 and VIII2 classes. Then the instruments used as data collection is using a questionnaire and managed using a correlational method then analyzed using product moment obtained by rxy = 0.172 compared with a significant level of 5% = 0.294 including the non-significant category with a coefficient of determination (kp) = 2.96% means that the parent economy contributes not significant to students' motivation to learn Mathematics. While the manager of data analysis is done by using linear regression which shows fcount ftabel = 1.307 4.075 Significant level a = 35.259 and b = 0.158 and n = 45 with one-sided test dk = n-2 = 43, so that ftabel = 4.075 . Seeing this condition, the hypothesis test rejects H0 and the recipient. Ha This study concludes that there is no significant influence between parents' economics on the motivation to learn Mathematics in Class VIII SMP Negeri 9 Padangsidimpuan.